Melatonin and Female Reproduction: An Expanding Universe - Olcese, James M. (Frontiers in Endocrinology, 2020)
For more than a half century the hormone melatonin has been associated with vertebrate reproduction, particularly in the context of seasonal breeding (Reiter 1980; Karsch et al 1984; Kauppila et al 1987; Johnston & Skene 2015). This association is due in large measure to the fact that melatonin secretion from the pineal gland into the peripheral circulation is a nocturnal event whose duration is reflective of night length, which of course becomes progressively longer during winter months and correspondingly shorter during the summer months. The nocturnal plasma melatonin signal is conserved in essentially all vertebrates and is accessed not just for reproductive rhythms, but for seasonal cycles of metabolic activities, immune functions, and behavioral expression (Wood & Loudon 2018). A vast literature on melatonin and vertebrate biology has accrued over the past 60 years since melatonin’s discovery, including the broad topic of animal reproduction, which is far beyond the scope of this human-focused review. Although modern humans in the industrialized world appear in general to have little remaining reproductive seasonality (Roenneberg & Aschoff, 1990; Rojansky et al 1992; Bronson 2004), the relationships between melatonin and human reproduction continue to attract widespread scientific attention. The purpose of this chapter is to draw attention to some newer developments in the field, especially those with relevance to human fertility and reproductive medicine. As the vast majority of studies have focused on the female reproductive system, a discussion of the potential impact of melatonin on human male fertility will be left for others (e.g. Fernando & Rombauts 2014; Frungieri et al 2017; Yu et al 2018).